PENGARUH KINERJA PENDAPATAN ASLI DAERAH DAN BELANJA MODAL TERHADAP KEMANDIRIAN KEUANGAN DAERAH - Ernawati, Ernawati; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to analyze (a) the influence of local own source revenue performance to the independencelevel of local finance, (b) the influence of capital expenditure to the independence level of local finance ondistricts/cities in East Java Province. The research method has been carried out by using quantitative method.The research samples are 35 districts/cities in East Java Province. The data is the secondary data which is in theform of the realization report of local budget of districts/cities in East Java Province in 2012-2015 observationperiods. The data has been obtained from the Audit Board of the Republic of Indonesia East Java ProvinceRepresentative. The data analysis has been done by using multiple linear regressions analysis. The result of theresearch proves that the performance of local own source revenue has positive influence to the independence levelof local finance. Capital expenditure has positive influence to the independence level of local finance ofdistricts/cities in East Java Province.Keywords: Local own source revenue performance, capital expenditure, the independence level of local finance